View from Ft. George, Trinidad - Martin, Barbara (Unimax Distributors Limited, 2010)
Photo showing a view of Port of Spain from Fort George. No. 303
Colour: Blue and Green Hues ; Style: Landscape ; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Port of Spain; Fort George